The transcontinental Maghreb : Francophone literature across the Mediterranean - Talbayev, Edwige Tamalet (Fordham University Press, 2017)
"The writer Gabriel Audisio once called the Mediterranean a "liquid continent." Taking up the challenge issued by Audisio's phrase, Edwige Tamalet Talbayev insists that we understand the region on both sides of the Mediterranean through a "transcontinental" heuristic. Rather than merely read the Maghreb in the context of its European colonizers from across the Mediterranean, Talbayev compellingly argues for a transmaritime deployment of the Maghreb across the multiple Mediterranean sites to which it has been materially and culturally bound for millennia. Studying a Mediterranean-inspired body of texts from Morocco, Algeria, Tunisia, and Gibraltar in French, Arabic, and Spanish, the book delivers provocative analyses that complicate the dichotomy between nation and Mediterranean, the valence of the postcolonial topos of nomadism in the face of postcolonial trauma, and conceptions of the Mediterranean as a mythical site averse to historical realization. In place of Albert Camus' colonialist Mediterranean utopia, Talbayev substitutes a trans-Mediterranean reading of Kateb Yacine's Nedjma as an allegory of the Maghreb's longstanding plurality. Through this adjusted Mediterranean genealogy, The Transcontinental Maghreb reveals these Mediterranean imaginaries to intersect with Maghrebi claims to an inclusive, democratic national ideal yet to be realized. Attuned to both the perpetual fluctuation of the Mediterranean as method and the political imperatives specific to the postcolonial Maghreb, the transcontinental reveals the limits of models of hybridity and nomadism oblivious to material realities. Through a sustained reflection on allegory and critical melancholia, the book shows how the Mediterranean decenters postcolonial nation-building projects and mediates the nomadic subject's reinsertion into a national collective respectful of heterogeneity. In engaging the space of the sea, the hybridity it produces, and the way it has shaped such historical dynamics as globalization, imperialism, decolonization, and nationalism, the book rethinksthe very nature of postcolonial histories and identities along its shores."--